Coatings Imparting Multifunctional Properties to Materials - Prorokova, N. P. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Coatings are traditionally used to protect materials from corrosion and erosion and improve the equipment's performance. At present, there are coatings that provide materials with new properties, for example, biocidal, hydrophobic and self-cleaning properties. A promising area of materials science is the development of "smart" coatings that simultaneously give materials several new properties. The coating propertiess are determined by the coatings' material, the structure and the properties of the substrate surface, and the methods of forming the coatings. This book contains the results of the latest research on the formation of coatings that impart complexes of new properties to various materials.